Synthesis, characterization, magnetic, thermal and redox properties of oxovanadium(IV) complex of heterocyclic acid hydrazone - Vijayan, Jyothy Gopurathinkal (European Journal of Chemistry, 2017)
The hydrazone ligand obtained from 2-thiophene carboxaldehyde and nicotinic hydrazide reacts with equimolar mixture of vanadyl acetyl acetonate in methanol to yield oxovanadium(IV) complex with 2-thiophenecarba nicotinic hydrazone. The prepared compound shows effective solubility in organic solvents such as acetonitrile, DMF and DMSO. Molar conductivity data of the complex revealed its non-electrolytic behavior in DMF and DMSO. EPR spectra of 2-thiophenecarba nicotinic hydrazonato oxovanadium(IV) was recorded in DMF at LNT and g and A values were calculated. The complex was proposed to be square pyramidal in geometry. Cyclic voltammogram of the complex in DMF was studied by changing the scan rates 50, 100, and 200 mV/sec. ΔE values of the complex showed the reversible criterion and ipc/ipa values which were close to 1 indicating that the redox couple as reversible. Thermogram of the complex was recorded to find the weight loss at different temperature ranges. Matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectra showed mass number of the molecular ions.